FACTORS AFFECTING EARNINGS MANAGEMENT IN MANUFACTURING COMPANIES LISTED ON INDONESIAN STOCK EXCHANGE - Gunawan, Syelly; Sufiyati , Sufiyati (Graduate Program of Universitas Tarumanagara, 2023)
This research aims to determine the effect of leverage, firm size, profitability, liquidity, information asymmetry, and earnings power on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) throughout 2018-2020. In this research 171 observational data are used in which obtained from 57 manufacturing companies that have met established criteria, where the samples are selected using purposive sampling technique. The data were calculated and processed using Microsoft Excel 2016 dan EViews 12. This research tested the classical assumption before testing the hypothesis and used the multiple linear regression model method, which the suitable model for this research is Fixed Effect Model (FEM). Leverage, profitability, and earnings power have significant effects on earnings management, while firm size, liquidity, and information asymmetry have insignificant effects on earnings management.